ANALISIS STRUKTUR VISUAL LAMBANG KOTAPRAJA JAMAN HINDIA BELANDA DARI PERSPEKTIF WACANA POSKOLONIAL - Novian Denny Nugraha; Sonson Nursholih (KalaTanda, 2016)
The simbol of municipality (big city) in Indonesia is changing from time to time, as well as changing according to the social and cultural conditions of the city. If in colonial era the simbol of the city is a representation of the power of the government or rule, and then the phenomenon is now beginning to change in the current era, where the simbol of the city functioned also for the needs of tourism. In the late Dutch East Indies colonial era around 1930s, some cities were considered to be self-reliant by government and economy, so that the government at that time made a simbol for the need to run the wheels of his government. The interesting phenomenon of the simbol of the city simbolically is the existence of simbols that are displayed, both simbols affiliated to the ruler (Dutch East Indies) and also the simbol that is a typical simbol of the city's local tradition. Composition and relationship between simbols in the city simbol is interesting to be studied and analyzed. Especially at visual structure area and meaning representation. The analysis is done by qualitative research method which is descriptive interpretative with semiotics theory approach for sign analysis and using postcolonial theory for understanding the meaning of the city simbol. The results of the analysis both in the visual structure and in the meaning shows the existence of different types of simbols that appear, as well as the discovery of the difference of simbol dominance in each simbol of the city. The relation between the simbols generated from the composition of the visual structure results in a new understanding, which in the postcolonial perspective will be interpreted by a binary opposition relationship, or the dominant/hegemonic relationship between the colonial government and the colony state, between â€œThe Otherâ€ and â€œThe Occidentâ€, or between colonizing and colonized countries. Furthermore, the simbolic relation on the visual structure and meaning resulted in the ideological significance of the sociocultural conditions of the community at that time.